JOB SEARCH ENGINE ONLINE PORTAL SYSTEM ARCHITECTURE - Prof. M. B. Patil; Swapnil S. Raut (International Engineering Journal For Research & Development, 2021)
Job Search Engine Online Portal System is designed to automate the Activities like filtering the resumes, storing the resumes, conducting the exam for suitable candidates and giving the results. This software package will help in eliminating the inefficient candidates and at the same time it provides to choose the best and suitable candidates for the required jobs. The existing system have the manual processing which takes the maximum time to filter the candidates qualifications, experience and conducting the exams, preparing the questions, answers for the jobs and processing the results. But By using this Computerization It can be done in a short period of time as well as in-time